2012
DOI: 10.5005/jp-journals-10024-1140
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life (OHQoL) among Adolescents Seeking Orthodontic Treatment

Abstract: Aim:The aim of this study was to assess the effect of different orthodontic treatment needs on the OHQoL of adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 17 publications
2
26
0
2
Order By: Relevance
“…Females scored higher means in four out of seven domains (domain 4, psychological discomfort; domain 4, physical disability; domain 5, psychological disability; domain 6, social disability; domain 7, handicap) along with the total score. Generally, the younger age group (12-19 years) scored higher means than did the older age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in five out of seven (domain 3, psychological discomfort; domain 4, physical disability; domain 5, psychological disability; domain 6, social disability; domain 7 handicap) as well as the total score. Table 3 shows the Spearman rank-order correlation coefficients between the DAI and OHIP-14 scores, which showed significant but almost no correlation (r 5 .176) between the two instruments at all grades of the DAI summative score.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Females scored higher means in four out of seven domains (domain 4, psychological discomfort; domain 4, physical disability; domain 5, psychological disability; domain 6, social disability; domain 7, handicap) along with the total score. Generally, the younger age group (12-19 years) scored higher means than did the older age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in five out of seven (domain 3, psychological discomfort; domain 4, physical disability; domain 5, psychological disability; domain 6, social disability; domain 7 handicap) as well as the total score. Table 3 shows the Spearman rank-order correlation coefficients between the DAI and OHIP-14 scores, which showed significant but almost no correlation (r 5 .176) between the two instruments at all grades of the DAI summative score.…”
Section: Resultsmentioning
confidence: 97%
“…9,12,16,17,[20][21][22][23][24] A study in Malaysia utilized IOTN as the instrument. 20 Most of these studies have focused on a specific group such as children, orthodontic patients, or patients seeking orthodontic care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Many studies have reported that malocclusion has a negative impact on adolescents' OHRQoL. 4,5 For esthetic reasons, malocclusion can play an important role in adolescents' psychological well-being and in their social acceptance and interaction. 6 In more severe cases, it can also result in functional limitations for the affected persons.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to orthodontic malocclusion treatment, it is important to consider patient's point of view and to appropriately set treatment priorities (1)(2)(3)(4)(5)(6). In determining treatment needs, the existing orthodontic indices emphasize the importance of the aesthetic component of malocclusions and the need to consider the psychosocial impact on patients' well-being (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%